2021
DOI: 10.1002/ejoc.202001635
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Molecular Properties of Partially Fluorinated DNTTs**

Abstract: octafluoro-dinaphthothienothiophene (F 8 DNTT) were synthesized via bisthiomethyl alkene intermediates which were accessible by McMurry coupling or Wittig olefination of partially fluorinated naphthalene precursors. DFT-based electronic structure calculations, near-edge X-ray absorption fine structure (NEXAFS) spectroscopy, and UV/Vis measurements were used for HOMO/LUMO gap determination and to analyze the electronic structures of the partially fluorinated DNTTs. Reduced exciton binding was observed in thin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(118 reference statements)
0
6
0
Order By: Relevance
“…In this study, we show that the recently synthesized partially fluorinated dinaphtothienothiophenes (F x DNTTs, x = 0, 4, 8) meet these requirements perfectly and thus enable such an investigation. [23] Since the modification of the electronic proper ties of noble metal surfaces by molecular adlayers has already been discussed in detail in the literature, [7,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37] which demon strates a controlled work function shift by organic mono and thin multilayer films, we only briefly describe our experimental and theoretical results on the work function changes of the Ag[Au](111) substrates investigated at the beginning in order to validate our methodology. In the next step, we then analyzed the modification of a low work function metal surface with the example of cesium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we show that the recently synthesized partially fluorinated dinaphtothienothiophenes (F x DNTTs, x = 0, 4, 8) meet these requirements perfectly and thus enable such an investigation. [23] Since the modification of the electronic proper ties of noble metal surfaces by molecular adlayers has already been discussed in detail in the literature, [7,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37] which demon strates a controlled work function shift by organic mono and thin multilayer films, we only briefly describe our experimental and theoretical results on the work function changes of the Ag[Au](111) substrates investigated at the beginning in order to validate our methodology. In the next step, we then analyzed the modification of a low work function metal surface with the example of cesium.…”
Section: Resultsmentioning
confidence: 99%
“…As depicted in Figure 1, the HOMO and LUMO levels of the F x DNTTs shift on a theoretical level toward lower energies with an increasing degree of fluorination, while the optical band gap remains almost constant in full consistency with experimental spectra. [23] The interface structure of the nonfluorinated DNTT on the noble metal surfaces Ag(111) and Au(111) was extensively studied previously yielding completely flatlying molecules with a molecular surface area of A = 1.3 nm 2 . [38,39] With this knowledge, we performed scanning tunneling microscopy measurements of all three DNTT derivatives on Ag(111), which are depicted in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…20−25 Such chemical modification can effectively lower the LUMO energy. 26,27 Moreover, previous studies showed that substitution of hydrogen atoms with fluorine ones changes the charge transport polarity in OFETs from the hole to the electron one, which is concluded to be due to a lowering of the frontier orbital energies. 28−33 Another possible explanation of this effect is the charge redistribution over the molecule 33,34 and formation of an array of microscopic dipoles 35 resulting in an ID (similarly to SAM) and thereby promoting injection of electrons and hindering injection of holes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the common methods for tuning the energies of the frontier molecular orbitals to E F is modification of the chemical structure of the conjugated organic molecules, for example, with electron-withdrawing groups, typically, with halogen-substituents such as cyanovinyl, chloro, fluoro, fluoroalkyl, and trifluoromethyl groups. Such chemical modification can effectively lower the LUMO energy. , Moreover, previous studies showed that substitution of hydrogen atoms with fluorine ones changes the charge transport polarity in OFETs from the hole to the electron one, which is concluded to be due to a lowering of the frontier orbital energies. Another possible explanation of this effect is the charge redistribution over the molecule , and formation of an array of microscopic dipoles resulting in an ID (similarly to SAM) and thereby promoting injection of electrons and hindering injection of holes …”
Section: Introductionmentioning
confidence: 99%
“…[50,51,[57][58][59] The substitution of H atoms by electrowithdrawing F atoms in π-conjugated organic systems is an effective means to altering the energy levels of the orbital frontiers, offering the possibility of tuning the electron transport properties, for example, by facilitating electron injection or converting an organic p-type semiconductor to an n-type in identical molecular structures. [60][61][62][63][64][65][66] Here, the direct and efficient synthesis of several new mesomorphous F-PAHs by nucleophilic fluorine substitution of arenes (S N FAr) [67] is reported. In addition, their self-organizational behaviors as well as their optical properties are analyzed and compared with their hydrogenated analogues with respect to the establishment of non-covalent perfluoroarene-arene intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%